Doing Business Over There Requires Savvy Conflict Resolution Management Here. Issue 11 (2nd December 2021) - Cunningham, James
Abstract : Commercial diplomacy—that is, leveraging the resources of the sovereign government in your firm's location to ensure a level playing field in the foreign markets in which the firm does business—is often an effective means of resolving, and in some instances preventing, disagreements that might otherwise fester into disputes.